Compact tunable dual-wavelength mid-infrared optical parametric oscillator pumped by high power gain-switched fiber laser. (4th June 2015) - Cai, Shuangshuang; Su, Jianjia; Wu, Pinghui; Hu, Chengzhi; Jiang, Peipei
Abstract: We report, to the best of our knowledge, the first demonstration of a gain-switched fiber laser pumped tunable dual-wavelength optical parametric oscillator (OPO) operating around 3–5  µ m. A homemade APMgLN crystal was used as the nonlinear material. A 'figure-of-h' shaped pump pulse was employed to improve the nonlinear conversion efficiency of the OPO. A maximum total idler output power of 4.82 W was obtained under pump power of 44.6 W with corresponding pump-to-idler conversion efficiency of 10.5%. The idler wavelengths were measured to be 3.34 and 3.65  μ m at a temperature of 40 °C, which can be successfully tuned with a rate of about 2 nm °C −1 by adjusting the working temperature of the APMgLN crystal from 20 °C to 80 °C.